Management Halaqoh Language To Improve Speaking Skills In Daarul Lughoh Wadda'wah Boarding School Bangil - Julisa Farah; Nuril Mufida (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Halaqah is one of the language learning programs used by Daarul Lughoh Wadda'wah Boarding School to make the learning efficient and effective. In this article, researchers describe how the impact of management halaqah itself against increased speaking skills, which contains the classification of students, planning, organization, and implementation. The book was used in halaqah is muhawaroh and husnul isgho’. This research belongs to descriptive qualitative research with a case study. The subject of this research is 250 students with 2 teachers force 2020/2021 in halaqah Daarul Lughoh Wadda'wah Boarding School Bangil. The data collection technique is done by interview, observation, and documentation does—data analysis techniques using the descriptive analysis technique of Miles and Huberman. The results in this study are as follows: 1) the application of halaqah Arabic in Daarul Lughoh Wadda'wah Boarding School consists of 2 levels, which is categorized to the first level of the named class i'dadi/beginners, which covers the junior high school students from class 1 to class 3, While for level 2 is called Al-Mutawassith which includes students of Senior High School. 2) planning of halaqah that has been set by the cottage, which is taken from the results of the meeting of monthly and semester. 3) the Implementation of halaqah applicable directly using talaqqi Kitab husnul isgho’ wherein such activity directly organized by qismu al-lughoh as well as on the sidelines of the given motivation in learning that is packed with the form of advice 4) Evaluation is done periodically, semester and yearly with the provision of the matter orally or syafahi. As for the management of halaqah impacts educational institutions and is perceived by students as members of halaqah and teachers as musyrif; this is evidenced by the rising of new students and the public confidence about the quality of their lives the boarding school). Halaqoh merupakan salah satu program Pembelajaran Bahasa yang dipakai oleh pondok pesantren Daarul Lughoh Wadda’wah untuk menjadikan sebuah pembelajaran yang efesien dan efektif.dalam artikel ini Peneliti mendeskripsikan bagaimana dampak manajemen halaqoh itu sendiri terhadap peningkatan maharoh kalam, yang didalamnya memuat tentang kelasifikasi siswa, perencanaan, organisasi dan implementasi.kitab yg dipakai dihalaqoh ini adalah kitab muhawaroh dan husnul isgho’. Penelitian ini termasuk penelitian kualitatif deskriptif dengan studi kasus. Subjek penelitian ini adalah 250 siswa dengan 2 guru angkatan 2020/2021 dihalaqoh pondok pesantren Daarul Lughoh Wadda’wah bangil. teknik pengumpulan data dilakukan dengan wawancara, observasi dan dukumentasi. Teknik analisis data menggunakan teknik analisis deskriptif Miles dan Huberman. Adapun hasil dalam penelitian ini adalah sebagai berikut: 1) penerapan halaqoh bahasa arab di Pondok Pesantren Daarul Lughoh terdiri dari 2 jenjang, yg akan dikategorikan untuk jenjang pertama dinamakan kelas i’dadi/pemula yang meliputi siswa SMP dari kelas 1 s/d kelas 3, Sedangkan untuk jenjang ke 2 dinamakan Al-Mutawassith yg meliliputi santri SMA/MA. 2) perencanaan dari halaqoh yg sudah ditetapkan oleh pondok yang diambil dari hasil rapat bulanan dan semester. 3) Pelaksanaan halaqoh diterapakan langsung dg cara talaqqi kitab husnul isgho’ dimana dalam kegiatan tersebut langung di organisir oleh bagian qismu al-lughoh serta disela-sela tersebut diberikan motivasi dalam pembelajaran yg dikemas dengan bentuk nasihat 4) Evaluasi dilakukan secara berkala, semester dan tahunan dengan pemberian soal secara lisan atau syafahi. Adapun manajemen halaqoh tersendiri berdampak baik terhadap institusi pendidikan dan dirasakan oleh santri sebagai anggota halaqoh dan guru sebagai musyrif, hal ini dibuktikan dengan meningkatnya peserta didik baru dan kepercayaan masyarakat tentang kwalitas Pondok).